THERMAL CHARACTERIZATION OF INDIUM DOPED ZINC OXIDE COATED KENAF/POLYANILINE/POLYLACTIC ACID HYBRID COMPOSITE - Sani, N.A.; Manaf, M.E.A.; Razak, J.A.; Shueb, M.I.; Doan, V.A. (Journal of Advanced Manufacturing Technology (JAMT), 2021)
The unique properties of conductive polymer composites such as electrical conductivity, biodegradability and mechanical strength enable them to be applied in various novel applications such as chemical sensors, fuel cell and shielding material. A combination of polylactic acid (PLA) with indium doped zinc oxide (IZO) coated kenaf fiber and polyaniline (PANI) appears as a potential approach for green-conductive composite development. However, a lower thermal stability of natural fiber reinforced polymer composite (NFRPC) is always the main issue despite its biodegradability and renewability. Thus, this study aims to analyze the effects of hybridization of PLA/IZO-Kenaf/PANI to the resulted thermal properties. In this study, hybrid composites were developed by melt-mixing followed with hot-pressing to form composite samples. The samples of each composition were analyzed by thermogravimetric analysis (TGA) and differential scanning calorimeter (DSC) for the decomposition temperature and transition temperature, respectively. Besides, the materials were also analyzed by X-ray diffraction (XRD) and Fourier-transform infrared (FTIR). The results from TGA has revealed an increase of 20.43% in thermal stability of PLA/IZO-Kenaf/PANI hybrid composite as compared than PLA-IZO-Kenaf composite. Meanwhile, the DSC results demonstrate an increase of melting temperature, Tm and melting enthalpy, ∆Hm which signifies higher heat resistance of hybrid composite as compared to PLA-Kenaf composite. Besides, changes on crystallinity and peaks of functional group of PLA and PLA polymers prove the interaction between the elements which leads to the variation of thermal properties.